Comparative study on data mining techniques used to predict risk of Heart Disease - Mhatre, Tejali Chandrakant; Varma, Satishkumar (International Journal of Engineering and Computer Science, 2019)
Heart disease is considered as one of the major causes of death throughout the world. Classification of heart disease can be valuable for medical practitioners to predict disease at early stage. To get accurate result of prediction of disease medical diagnosis system very useful. There are different data mining techniques available to classify medical data related to heart disease. In this paper, survey is carried out to find which are different data mining techniques can be used for heart disease prediction system.